2017
DOI: 10.1093/jee/tox312
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Possible Pheromones of Cerambycid Beetles by Field Testing Known Pheromone Components in Four Widely Separated Regions of the United States

Abstract: The pheromone components of many cerambycid beetles appear to be broadly shared among related species, including species native to different regions of the world. This apparent conservation of pheromone structures within the family suggests that field trials of common pheromone components could be used as a means of attracting multiple species, which then could be targeted for full identification of their pheromones. Here, we describe the results of such field trials that were conducted in nine states in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Field studies conducted in the eastern USA, where P. testaceus was introduced many decades ago (Swift and Ray 2010), have revealed inconsistent responses to the two compounds. For example, adults of P. testaceus were attracted in significant numbers to traps baited with 3-hydroxy-2-hexanone alone during bioassays that lacked a 2-methyl-1-butanol treatment, but only the latter compound was attractive when both compounds were presented as single compound treatments in other bioassays (Hanks and Millar 2013; Hanks et al 2018, 2019; Millar et al 2018). Other field trials conducted in the eastern USA, with traps baited with blends of cerambycid pheromones that included 2-methyl-1-butanol and 3-hydroxy-2-hexanone (Handley et al 2015; Hanks and Millar 2013), have also demonstrated significant attraction of P. testaceus to these blends.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies conducted in the eastern USA, where P. testaceus was introduced many decades ago (Swift and Ray 2010), have revealed inconsistent responses to the two compounds. For example, adults of P. testaceus were attracted in significant numbers to traps baited with 3-hydroxy-2-hexanone alone during bioassays that lacked a 2-methyl-1-butanol treatment, but only the latter compound was attractive when both compounds were presented as single compound treatments in other bioassays (Hanks and Millar 2013; Hanks et al 2018, 2019; Millar et al 2018). Other field trials conducted in the eastern USA, with traps baited with blends of cerambycid pheromones that included 2-methyl-1-butanol and 3-hydroxy-2-hexanone (Handley et al 2015; Hanks and Millar 2013), have also demonstrated significant attraction of P. testaceus to these blends.…”
Section: Discussionmentioning
confidence: 99%
“…The growing evidence that fuscumol and its analogues appear to be conserved pheromone structures within both the subfamilies Spondylidinae and Lamiinae (e.g. 27,7681 ) also has major implications for invasion biology. Specifically, it is a prerequisite for reproduction that males and females encounter each other and mate, but the sexes are less likely to locate one another successfully at low densities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical viewpoint, this parsimony implies that multiple cerambycid species may be attracted to traps baited with single components or blends of related pheromone components [4][5][6][7][8][9][10]. As such, these pheromones are finding increasing use in the delineation of the geographic ranges of native species [11], and in surveillance programs for detecting exotic species [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, wood-boring cerambycid beetles are of major importance as potential invaders, because of the ease with which they are transported between continents in wooden products and packing materials by global commerce [9,10,12]. This parsimony also implies that the identification of pheromone components for one cerambycid species may subsequently expedite the identification of pheromones or likely pheromones for related target species [8,13,14].…”
Section: Introductionmentioning
confidence: 99%